2019
DOI: 10.1111/jmwh.12975
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Intrapartum Interventions and Cesarean Birth in Low‐Risk Nulliparous Women with Spontaneous Onset of Labor

Abstract: Introduction: Cesarean birth rates vary widely across hospitals in the United States, even among women who are considered low-risk for the procedure. This variation has been attributed to differences in health care provider practice, but few studies have explored patterns of labor management in relation to cesarean birth. Methods: This was a retrospective observational study of 26,259 nulliparous, term, singleton gestation, vertex presentation births following spontaneous onset of labor. Births occurred from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The association has also been found even when controlling for pregnancy risk [20] and other different interventions associated with oxytocin administration [9].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The association has also been found even when controlling for pregnancy risk [20] and other different interventions associated with oxytocin administration [9].…”
Section: Discussionmentioning
confidence: 91%
“…In Spain, a study to evaluate the implementation of the Normal Birth Care Strategy shows a rate of 19.4% IOL and 53.3% AOL, amply surpassing its recommendations [6]. A Swedish study observed a 33% oxytocin use [7], while a French study showed a rate above 60% [8] and in the United States, Iobst et al reported that 44% of low-risk nulliparous women had oxytocin administered during labor [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, birth interventions impact the pregnant women's satisfaction with childbirth. 4,5 Considering these negative effects, the timing of admission to the delivery room is crucial. This study found that multiparous pregnant women experienced higher labor satisfaction compared to primiparous women, and women who desired their pregnancy reported higher labor satisfaction than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…4 Preventing unnecessary cesarean sections and other invasive deliveries can largely be achieved by delaying hospital admission until the onset of the active labor phase. 5 Traditional criteria for admitting pregnant women to the delivery room include complete cervical effacement, dilation of 3 cm or more, other cervical changes, and spontaneous rupture of membranes. 6 However, it has been observed that obstetric interventions during labor are fewer when cervical dilation is 6 cm or more.…”
Section: Introductionmentioning
confidence: 99%
“…Although women admitted for induction of labor require some interventions to initiate and maintain labor progression, those admitted after spontaneous onset of labor have already begun the physiologic processes of labor and should not require the same level of intervention. For this reason, high rates of interventions among women admitted after spontaneous onset of labor raise concern because evidence shows an association between the use of multiple intrapartum interventions and cesarean birth …”
Section: Introductionmentioning
confidence: 99%